Assessment of the impact of implementation research on the Visceral Leishmaniasis (VL) elimination efforts in Nepal. - Anand Ballabh Joshi; Megha Raj Banjara; Sachi Chuke; Axel Kroeger; Saurabh Jain; Abraham Aseffa; John C Reeder (Public Library of Science (PLoS), 2023)
Nepal, Bangladesh, and India signed a Memorandum of Understanding (MoU) in 2005 to eliminate visceral leishmaniasis (VL) as a public health problem from the Indian subcontinent by 2015. By 2021, the number of reported VL cases in these countries had declined by over 95% compared to 2007. This dramatic success was achieved through an elimination programme that implemented early case detection and effective treatment, vector control, disease surveillance, community participation, and operational research that underpinned these strategies. The experience offered an opportunity to assess the contribution of implementation research (IR) to VL elimination in Nepal. Desk review and a stakeholder workshop was conducted to analyse the relationship between key research outputs, major strategic decisions in the national VL elimination programme, and annual number of reported new cases over time between 2005 and 2023. The results indicated that the key decisions across the strategic elements, throughout the course of the elimination programme (such as on the most appropriate tools for diganostics and treatment, and on best strategies for case finding and vector management), were IR informed. IR itself responded dynamically to changes that resulted from interventions, addressing new questions that emerged from the field. Close collaboration between researchers, programme managers, and implementers in priority setting, design, conduct, and review of studies facilitated uptake of evidence into policy and programmatic activities. VL case numbers in Nepal are now reduced by 90% compared to 2005. Although direct attribution of disease decline to research outputs is difficult to establish, the Nepal experience demonstrates that IR can be a critical enabler for disease elimination. The lessons can potentially inform IR strategies in other countries with diseases targeted for elimination.